Imaginal cestodiasis - S. B. Chuelov; A. L. Rossina (LLC "Diagnostics and Vaccines", 2022)
The urgency of the problem of cestodiases is due to the widespread prevalence and the ability of cestodes to infect a person.The aim and result of the work is to summarize the available information on the etiology, epidemiology, pathogenesis, clinical picture, diagnosis, etiotropic therapy and prevention of some imaginal cestodoses (bertielliasis, railietiniasis, dipylidiasis, hymenolepiasis, drepanidotheniasis, rodentolepiasis,  mesocestoidiasis, hydatigeriasis) recorded in humans.Various cestodoses are widespread throughout the world, including in Russia. The clinic mainly includes symptoms of lesions of the gastrointestinal tract,  allergic reactions. Diagnostics is carried out on the basis of a set of clinical and laboratory-instrumental indicators. Prevention is carried out taking into account the characteristics of the epidemiology.